2008
DOI: 10.1002/aic.11596
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics simulation studies of CO2 – [bmim][PF6] solutions: Effect of CO2 concentration

Abstract: in Wiley InterScience (www.interscience.wiley.com).Molecular dynamics simulations have been carried out on CO 2 -[bmim] [PF 6 ] mixtures using a refined atomistic potential model for the ionic liquid, at different concentrations of CO 2 . The expansion in volume as a function of added CO 2 was found to agree well with experiments at all but the highest concentration. Significant concentration dependent differences in the radial distribution function of CO 2 around the anion have been observed. These differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
51
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(62 citation statements)
references
References 68 publications
10
51
1
Order By: Relevance
“…6 ]. 30 For instance, the position of the first peak in the anionÀanion RDF shifted from 6.5 to 8.1 Å for 0 and 70 mol % CO 2 in [bmim][PF 6 ]. 30 To investigate the effects of CO 2 concentration on [BF 4 ] À À[BF 4 ] À interactions, the RDFs and coordination numbers of BÀB were studied.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…6 ]. 30 For instance, the position of the first peak in the anionÀanion RDF shifted from 6.5 to 8.1 Å for 0 and 70 mol % CO 2 in [bmim][PF 6 ]. 30 To investigate the effects of CO 2 concentration on [BF 4 ] À À[BF 4 ] À interactions, the RDFs and coordination numbers of BÀB were studied.…”
Section: Resultsmentioning
confidence: 99%
“…30 For instance, the position of the first peak in the anionÀanion RDF shifted from 6.5 to 8.1 Å for 0 and 70 mol % CO 2 in [bmim][PF 6 ]. 30 To investigate the effects of CO 2 concentration on [BF 4 ] À À[BF 4 ] À interactions, the RDFs and coordination numbers of BÀB were studied. As shown in Figure 6a, the absorption of CO 2 up to a mole fraction of 0.1 had no effect on the BÀB RDF, and the positions of the first peaks were both at 7.67 Å for x 2 = 0 and 0.1.…”
Section: Resultsmentioning
confidence: 99%
“…That this property is indeed primarily determined by the identity of the anions rather than by modifications of imidazolium-based cations has been confirmed in numerous studies. [6][7][8][9][10][11][12][13][14][15] Regarding anions, it was found that CO 2 solubility increased in the order of BF 4 -< TfO -< TfA -< PF 6 -< Tf 2 N -< C 7 F 15 CO 2 -< eFAP -< bFAP -. 4 In another study the following trend of increasing CO 2 solubility was found: NO 3 -< SCN -< Me- 26 Generally, ILs that contained fluorinated anions tended to exhibit higher CO 2 solubilities compared with non-fluorinated anions.…”
Section: Introductionmentioning
confidence: 99%
“…It has been known that several room temperature ionic liquids (RTILs) dissolve carbon dioxide (CO 2 ) significantly at high CO 2 pressures, and the phase behavior and the structure of the solution have been extensively studied experimentally and theoretically until now [1][2][3][4][5][6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%